Phosphorylation of streptozotocin during uptake via the phosphoenolpyruvate: sugar phosphotransferase system in Escherichia coli. - Ammer, J (Antimicrob Agents Chemother, 1979)
Mutants of Escherichia coli K-12, Staphylococcus aureus, and Bacillus subtilis defective in the general components (enzyme I, or HPr, or both) of the phosphoenolpyruvate:sugar phosphotransferase system are shown to be resistant to the antibiotic streptozotocin. It is shown here, employing 32P-labeled phosphoenolpyruvate, that wild-type cells of E. coli phosphorylate streptozotocin, whereas with a phosphotransferase system-defective mutant of E. coli the drug is recovered in an unaltered, free form. The internal accumulation of streptozotocin at the steady-state level was about 70 times that of the concentration in the external medium. The antibacterial action of streptozotocin, as well as the uptake of the drug, was inhibited by N-acetyl-D-glucosamine. The uptake of the antibiotic was extremely sensitive to p-chloromercuribenzoate. It is concluded that streptozotocin is taken up by E. coli via the phosphoenolpyruvate:sugar phosphotransferase system and consequently accumulates in the cell at first as streptozotocin-phosphate.